2015
DOI: 10.13189/ujmr.2015.030402
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Growth and Identification of Chlorpyrifos Degrading Bacteria from Agricultural Soil in Anambra State, Nigeria

Abstract: The extensive use of pesticides is one of the major causes of pollution of soil and water environments. The current method for removing such contaminants from the environment through biodegradation has been shown to be more effective than any other method. Three pesticide degrading bacteria were isolated and identified through cultural and biochemical tests as strains of Pseudomonas aeruginosa, Serretia marcescens and Klebsiella oxytoca. Their growth in mineral salt medium supplemented with 20mg/l of Chlorpyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…and especially P. aeruginosa reduce the concentration of chlorpyrifos concentration by 42%. Ifediegwu et al (2015) also stated that the reduction in chlorpyrifos concentration by P. aeruginosa was 60%. Xia et al (2013) showed that Serratia sp.…”
Section: Discussionmentioning
confidence: 99%
“…and especially P. aeruginosa reduce the concentration of chlorpyrifos concentration by 42%. Ifediegwu et al (2015) also stated that the reduction in chlorpyrifos concentration by P. aeruginosa was 60%. Xia et al (2013) showed that Serratia sp.…”
Section: Discussionmentioning
confidence: 99%
“…The flasks were incubated on a rotary shaker at 150rpm at 30 0 C for 28 days. The optical density of the isolates was determined at intervals of 4 days for 28 days using Spectrophotometer (OD 600nm) as described by [2].…”
Section: Molecular Identification Of Isolatesmentioning
confidence: 99%
“…, used on grain, cotton, fruit, and vegetable crops, as well as, lawns and ornamental plants [2], against common pests like moths, hoppers, midges, worms and spiders [3]. The use of Pesticide has greatly improved crop productivity and reduced reduction of crop yield.…”
mentioning
confidence: 99%
“…Organophosphate pesticides have been linked to various health effects, including cancer, nausea, and headaches, and are associated with endocrine disruption, reproductive health concerns, and neurotoxic effects with long-term exposure (Geed et al, 2017). Organophosphate residues in food are linked to various cases of food poisoning recorded in different parts of the world (Ifediegwu et al, 2015;Uniyal et al, 2021;Ambreen & Yasmin, 2021). Milk is an ideal food for dissolving organic pollutants, including pesticides, due to its lipophilic properties (Nasef et al, 2019;Rêgo et al, 2019).…”
Section: Impact Of Organophosphate Residues On Healthmentioning
confidence: 99%